Development of Efficient Frequency and Sensitivity of Transducer on Flaw Measurement by Using Ultrasonic Testing Method on Thin Carbon Steel Plate - M. Yusup, Eliza; Baduhalin, Muhammad Adam; Abdul Rani, Abdul Syahmie Azri; Jamil, Jeffry; Saniman, Muhammad Nur Farhan (International Journal of Integrated Engineering, 2024)
Throughout several decades, welded pipes are some of the critical areas that required scheduled inspection. The Ultrasonic Testing Flaw Detector (UTFD) method of Non-Destructive Testing (NDT) is one of the reliable technologies for early detection of any internal flaw that would present an impressive danger. The objective of the research is to determine the selection of transducer in detecting defect at Carbon Steel sample with single Vee butt joint. The experimental work in this study is using two different frequencies of transducer, which are 2MHz and 4Mhz. Each of the transducer represent by three different angles, which are 45°, 60° and 70°. The sample with thickness, t = 12mm is inspected with several types of scanning movement including depth, swivel, orbital and lateral scanning. Other parameter involves is different sensitivity of the transducer by controlling the gain of the machine. From the observation of the results, the sensitivity is directly proportional with the angle of the transducer, where for 4MHz, the readings for gain at 45°, 60° and 70° angles are 43.30 dB, 47.50 dB and 48.30 dB, respectively. At the end, it can be concluded that 4MHz transducer of 60° angle provide the most accurate measurement of flaw detector compared with other angles. Furthermore, this research also shows that when the frequency is increase, it produces shorter wavelength and better resolution with shorter beam spread compared to low frequency transducer.